Partisipasi Masyarakat dalam Pengelolaan Sampah di Kelurahan Pasie Nan Tigo Kecamatan Koto Tangah Kota Padang - Rahayu, Refi Gustri; Nefilinda, Nefilinda; Febriani, Trina (UNIVERSITAS NEGERI MAKASSAR, 2023)
This study aims to analyze and describe how the community participates in waste reduction and handling in Pasie Nan Tigo Village, Koto Tangah District, Padang City. This type of research is quantitative. The research population is the community in Pasie Nan Tigo Village, Koto Tangah District, Padang City with a sample of 63 families, in this study using purposive random sampling and data analysis techniques used descriptive analysis. The results of the study: 1) Community participation in waste reduction in Pasie Nan Tigo Village, Koto Tangah District, Padang City in the